Bowel function, mental health, and psychosocial function in adolescents with Hirschsprung's disease. Issue 2 (1st February 1997) - Diseth, Trond H; Bjørnland, Kristin; Nøvik, Torunn S; Emblem, Ragnhild
Abstract : Congenital intestinal malformations are uncommon and may pose lasting somatic difficulties. Patients with anorectal anomalies have a high frequency of persistent faecal dysfunction and psychosocial problems. This study examined whether adolescents with Hirschsprung's disease have more psychosocial problems than their healthy peers. Nineteen adolescents (mean age 15.7 years) with Hirschsprung's disease were assessed for bowel function, anorectal physiology, mental health, and psychosocial functioning by physical examinations, semistructured interview, and standardised questionnaires. The adolescents were compared with controls. The parents of 13 adolescents with Hirschsprung's disease were interviewed and completed questionnaires. Thirty two per cent of the adolescents with Hirschsprung's disease had significant impairment of continence, but no more psychopathology (16%) nor psychosocial dysfunction as a group than their healthy peers. Faecal incontinence was associated with poorer psychosocial functioning and parental criticism. The fact that a significant number of patients with Hirschsprung's disease have incontinence into adulthood indicates the need for parental counselling, encouraging realistic expectations about continence.